Subcloning of Mycobacterium tuberculosis KatG gene in bacterial expression system" - Mohd Hamzah, Mohd Nasir (Universiti Sains Malaysia, 2006)
KatG is the gene in Mycobacterium tuberculosis which responsible for encoding of catalase peroxidase enzyme to enable its survival in host macrophage. KatG also reported to play an important role in enabling the killing effect of the antituberculous pro-drug, isoniazid (IN H). The mutation of this gene has been reported to create resistancy of Mycobacterium tuberculosis toward INH treatment. Since the killing effect of the drug has a significant relation with this gene, the structure and properties of KatG should be study for further information. EcoRI restriction enzyme was found to produce 2252 bp of DNA product. The gene was then sliced out from pCR®2.1-TOPO by using EcoRI restriction enzyme and ligated into a high-level protein expression vector, pRSET for expression assay. The recombinant sequenced has been confirmed by EcoRIPvull restriction analysis. The gene has also been sequenced by cycle sequencing and the primers are M13F, M13R, KG3 and KGS.